ANALYSIS FOR POTENCY AND PRODUCTION OF GRANULE ORGANIC FERTILIZER BASED ON MANURE - Firman L. Sahwan (BPPT)
Organic materials that are generally used as raw material for organic fertilizer granules (POG) is a natural organic material that has been degrade, smooth and dry. One of the main raw materials are always used with a very high percentage of usage, is manure. Manure potential in Indonesia is very high, amounting to 113.6 million tons per year, or 64.7 million tons per year to the island of Java. From this amount, it will be generated numbers POG production potential of 17.5 million tons per year (total Indonesia) or 9.9 million tons per year for the island of Java. While the realistic POG production predictions figures made from raw manure is 2.5 million tons annually, a figure that has been unable to meet the number requirement of POG greater than 4 million tons per year. Therefore, in producing POG, it should be to maximize the using of the potential of other organic materials so that the use of manure can be saved. With the use of a small amount of manure (maximum 30% for cow manure), it would be useful also to avoid the production of POG with high Fe content.keywods: organic material, manure, granule organic fertilizer